2015
DOI: 10.1007/s10120-015-0464-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for selection of patients at high risk of recurrence or death after complete surgical resection in stage I gastric cancer

Abstract: Background The therapeutic benefit of adjuvant chemotherapy has not been proven in stage I gastric cancer (GC). The aim of this study was to identify stage I GC patients at high risk of recurrence or death. Results With a median follow-up of 54 months (range 0-60 months), 212 patients (7.6 %) experienced recurrence or death, and the 5 -year recurrence-free survival (RFS) rate and overall survival rate were 89.9 and 93.4 %, respectively. With a multivariate analysis, six factors (age over 65 years, male gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 29 publications
5
41
1
Order By: Relevance
“…Several trials have addressed the effect of the recovery period following curative surgery and start of adjuvant therapy as potential contributors to outcome in other cancers including breast , colorectal , and gastric . In breast cancer, there were conflicting reports, with no difference in disease‐free survival or OS in patients who received adjuvant chemotherapy within the arbitrary cut‐off of 21 days after surgery .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials have addressed the effect of the recovery period following curative surgery and start of adjuvant therapy as potential contributors to outcome in other cancers including breast , colorectal , and gastric . In breast cancer, there were conflicting reports, with no difference in disease‐free survival or OS in patients who received adjuvant chemotherapy within the arbitrary cut‐off of 21 days after surgery .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this study's findings, while "timely" AT should remain the clinical goal after safe recovery for those who undergo upfront pancreatectomy, one should not forego intended AT simply because the initiation date is beyond the theoretical 8-week "window." Several trials have addressed the effect of the recovery period following curative surgery and start of adjuvant therapy as potential contributors to outcome in other cancers including breast [15], colorectal [16], and gastric [17,18]. In breast cancer, there were Journal of Surgical Oncology conflicting reports, with no difference in disease-free survival or OS in patients who received adjuvant chemotherapy within the arbitrary cutoff of 21 days after surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, patients with curative gastrectomy continue to experience recurrence during follow-up. More recent studies have shown that the overall 5-year survival rate of gastric cancer has improved because of curative gastrectomy with chemotherapy (2,3). However, death from gastric cancer is almost entirely caused by recurrent diseases (4).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported that submucosal layer invasion, lymph node metastasis, and pathological differentiation (tub1 and tub2) were the risk factors for tumor recurrence after surgery for early stage GC 43. On the other hand, another previous study revealed that high age, male, lymphovascular invasion, stage IB (proper muscle invasion or lymph node metastasis), perineural invasion, and elevated tumor marker were independent poor prognostic factors for RFS 44. Although we did not investigate the relationship between GAR and these clinical characteristics of stage I GC which was associated with tumor recurrence, our result indicated that preoperative high GAR (>0.80) was useful for predicting poor prognosis of RFS in stage I GC patients in comparison with low GAR (<0.80).…”
Section: Discussionmentioning
confidence: 96%
“…The recurrence rate in patients with early stage GC was reported to be 1.4%‐3.0% 43, 44. Previous study reported that submucosal layer invasion, lymph node metastasis, and pathological differentiation (tub1 and tub2) were the risk factors for tumor recurrence after surgery for early stage GC 43.…”
Section: Discussionmentioning
confidence: 99%